The Gulf of Tonkin : the United States and the escalation in the Vietnam War - Tovy, Tal (New York, NY : Routledge, 2021)
"The Gulf of Tonkin: The United States and the Escalation in the Vietnam War analyzes the events that lead to the escalation of the conflict in Vietnam and increased American involvement. On August 4, 1964, the captains of two American destroyers, the USS Maddox and the USS Turner Joy, reported that their ships were attacked by North Vietnamese torpedo boats. This report came on top of a previous report by the captain of the USS Maddox, indicating that he had been attacked by torpedo boats two nights earlier. The text introduces readers to the historiography of these incidents and how the perception of the events changed over time. The attacks, which were collectively called 'The Gulf of Tonkin Incident,' are presented in the context not only of the Vietnam War, but also the Cold War and the United States government powers, allowing students to understand the events' full ramifications. Using essential primary documents, Tal Tovy provides an accessible introduction to a vital turning point in U.S. and international affairs. This book will be useful to all students of the Vietnam War, American military history, and foreign policy history"--
The Road to Vietnam: The United States Foreign Policy after World War II -- Setup: The United States and Vietnam (1954-1963) -- From Dallas to Tonkin: The Critical Moment -- The White House vs. Capitol Hill: The War Powers Act.
OCLC-licensed vendor bibliographic record.
Keywords: Tonkin Gulf Incidents, 1964.; Vietnam War, 1961-1975.; United States -- Foreign relations -- 1953-1961.; War and emergency powers -- United States; Operation Rolling Thunder, 1965-1968.; Vietnam War, 1961-1975 -- Historiography; HISTORY / Military / Vietnam War; HISTORY / United States / 20th Century; HISTORY / Modern / 20th Century